Managing Extreme Evaluation Anxiety Through Nonverbal Communication - Regina S. Schinker (The Evaluation Center at Western Michigan University, 2005)
"Many evaluative situations cause people to fear that they will be found to bedeficient or inadequate by others..." (Donaldson, Gooler, & Scriven, 2002, p. 261). Donaldson, et al. (2002) use the acronym XEA to describe excessive anxiety and explain that "...there are people who are very upset by, and sometimes rendered virtually dysfunctional by, any prospect of evaluation, or who attack the evaluation without regards to how well conceived it might be" (ibid). A common technique or 'magic bullet' to prevent excessive anxiety would not exist in program evaluation.